2016
DOI: 10.1016/j.surg.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Medical telementoring using an augmented reality transparent display

Abstract: Background The goal of this study was to design and implement a novel surgical telementoring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 14 publications
0
63
0
1
Order By: Relevance
“…During preliminary testing, we found that a fixed platform (as opposed to a head-mounted camera) improved spatial orientation and communication between the mentor and the operator. Andersen et al reported that a similar set-up (STAR: System for Telementoring with Augmented Reality) decreases operator focus shifts and improves accuracy when performing port placement and abdominal incisions on a surgical simulator 23. Telementoring of trained surgeons learning new procedures appears to yield similar complication rates and surgical duration compared with on-site mentoring 24.…”
Section: Discussionmentioning
confidence: 99%
“…During preliminary testing, we found that a fixed platform (as opposed to a head-mounted camera) improved spatial orientation and communication between the mentor and the operator. Andersen et al reported that a similar set-up (STAR: System for Telementoring with Augmented Reality) decreases operator focus shifts and improves accuracy when performing port placement and abdominal incisions on a surgical simulator 23. Telementoring of trained surgeons learning new procedures appears to yield similar complication rates and surgical duration compared with on-site mentoring 24.…”
Section: Discussionmentioning
confidence: 99%
“…This customized lexicon was developed for use in the medical telementoring application STAR, in which the mentor or expert is provided with multimodal interactions, including touch-based annotations, air gestures, and tool manipulation to guide a novice surgeon or trainee through a procedure (Andersen et al, 2016).…”
Section: Data Set 1: Image Manipulation (Imd)mentioning
confidence: 99%
“…Interactive additions to telementoring systems such as telestration, laser pointing capabilities, or increased remote control of the visual field have played a role in enriching the teaching capabilities of the remote surgeon. Wearable technology, such as the Google Glass (Google, Mountainview, CA), and methods of augmented reality telementoring have also been implemented and have had some success (25,26). Specially designed telemedical robotic platforms such as the Karl Storz Endoscopy-America, Inc. VisitOR1 (Karl Storz; Tuttlingen, German) and RemotePresence-7 robot (InTouch Health; Santa Barbara, Calif) have been developed and may play a role in further increasing the remote surgeon's presence in the operating room.…”
Section: Current Applicationsmentioning
confidence: 99%
“…They found that the students trained using the augmented reality platform had significantly faster skill acquisition as compared to students trained with traditional mentoring. Similarly, Andersen et al developed a System for Telementoring and Augmented Reality (STAR) that provided visual instruction to a monitor that the students used to visualize their operating field in order to evaluate its effectiveness in training tasks including a port placement and abdominal incision (26). The participants using STAR had decreased errors and focus shifts but took longer to complete the tasks as compared to those with traditional mentoring.…”
Section: Augmented Realitymentioning
confidence: 99%